Linking Local Government and Demographics to Ecological Footprint - Muhammad Abduh Abduh; Dedik Budianta; Arinafril Arinafril; Lili Erina (Sriwijaya Journal of Environment, 2020)
To simplify the description of the damage phenomenon to the earth, the concept of ecological footprint can be used. This concept is not specifically built to calculate the destruction of the earth. This concept calculates how much space (on land and water) humans need to produce the resources they need including absorbing the waste they produce. This study calculates the ecological footprint in Palembang and its surroundings according to demographic factors and local government.  To investigate the general pattern of ecological footprint and its determinants based on the respondents’ reports, a survey was launched in October 2017. As a result, the average ecological footprint in Palembang Metropolitan and its surroundings is 0.591 global hectares (gha).  The ecological footprint in Palembang Metropolitan and its surroundings is formed by 4 things, namely: diet and food choices, shelter/home life, transportation and lifestyle choices.  The largest portion is given by diet and food choices (26.8 percent), while the smallest contribution is contributed by transportation (24.1 percent).   Taking into account demographic factors, a high ecological footprint is owned by a group of male individuals, aged 30-39 years, highly educated, working, and after hearing and understanding climate change and ecological footprint. Finally, if observed according to the type of government, metropolitan cities have a high ecological footprint than others.  Finally, the ecological footprint of Palembang as a metropolitan city is higher than the others.